IMPROVING STUDENTS’ LEARNING CONCENTRATION IN ACCOUNTING THROUGH THE INTEGRATION OF JIGSAW AND DIFFERENTIATED INSTRUCTION METHODS IN CLASS Z AKL SMK BATIK 1 SURAKARTA - Saputra, Ridwan Cahya; Winarsih, Sri; Sari, Dhany Efita; Murtiningsih, Murtiningsih (Buletin Literasi Budaya Sekolah, 2025)
Learning concentration is a critical factor influencing the success of the educational process. Without optimal concentration, students tend to absorb information poorly, negatively impacting their comprehension and academic achievement. Various factors can affect concentration, such as fatigue or tension due to the difficulty of learning materials. Therefore, an interactive and collaborative approach that meets students’ individual needs is essential in accounting education. This research explores the use of a combined approach using the Jigsaw method and Differentiated Instruction to enhance student concentration in learning. This Classroom Action Research (CAR) employed a qualitative approach and was conducted in two cycles. The results showed a 20% improvement in the cognitive domain - rising from 60% in cycle I to 80% in cycle II. Affective and psychomotor indicators also improved by 20% - from 50% in cycle I to 70% in cycle II. These findings indicate that combining the Jigsaw method with Differentiated Instruction can effectively enhance student concentration in accounting learning.